Antiplatelet agents and anticoagulants increased the bleeding risk of bedside percutaneous dilational tracheostomy in critically ill patients - Yen-Hsiang Huang; Chien-Hua Tseng; Ming-Cheng Chan; Bor-Jen Lee; Chih-Hung Lin; Gee-Chen Chang (Journal of the Formosan Medical Association, 2020)
Background: The main objective of this study was to investigate the safety of bedside percutaneous dilational tracheostomy (PDT) by pulmonologists in critically ill patients, and the factors associated with complications resulting from PDT. Methods: We retrospectively enrolled critically ill patients who had undergone bedside PDT in the intensive care units (ICUs) and respiratory care center from February 2016 to December 2018. Results: A total of 312 patients were included for analysis, with a mean age of 69.6 ± 17.7 years. Two hundred and eight of the patients were male (66.7%). The mean acute physiology and chronic health evaluation II score was 25.3 ± 6.3, and the mean body mass index was 22.4 ± 4.2. Most of the patients were intubated due to respiratory disorders (51.3%). Fifty-six patients (17.9%) received antiplatelet agents or an anticoagulant regularly prior to PDT. All enrolled patients were undergone bedside PDT successfully. The total complication rate of PDT was 14.4%. Patients who took antiplatelet agents or anticoagulants regularly before PDT had a higher risk of bleeding than patients who went without (26.8% versus 7.0%, adjusted odds ratio 4.93 [95% f 2.16–11.25], p < 0.001). Finally, a longer length of intubation resulted in a higher probability in the length of ICU stay being ≧28 days (adjusted odds ratio 1.11 [95% CI 1.08–1.14], p < 0.001). Conclusion: Our study demonstrated that it was feasible for pulmonologists to perform bedside PDT in critically ill patients. However, antiplatelet agents and anticoagulants use increased the risk of bleeding in PDT patients.